STRATEGIC POLICY DIRECTIONS OF MICRO SMALL MEDIUM BUSINESS IN THE DIGITAL ECONOMY ERA - Atsari Sujud; Muhammad Ivan (JURNAL BISNIS STRATEGI, 2022)
Firms of all sizes, across all sectors, are increasingly equipping their staff with digital tools. Today, over half of firm's employees use computers with Internet access, including Micro, Small and Medium Enterprises (MSMEs). The purpose of this study is to determine the impact of digital economy on the MSMEs Performance in Indonesia. This study used a descriptive exploratory and literature review approaches. The theory construct is carried out by referring to several sources, such as books, scientific journals and papers. The results of the study shows that the rapid development of digital technology, apart from being a challenge for the business world, is also a huge opportunity and potential for increasing MSMEs Performance. Another finding is that the need for digital infrastructure development continue to be accelerated the process of using quality and sustainable digital technology. Digital infrastructure will linearly support inclusive and sustainable industrialization to encourage innovation. Recommendations for MSME business development require a long-term MSME development policy scheme to ensure that MSME performance continues to contribute optimally and have signigicant impact on improving the national economy even to the lowest ranks, namely rural communities.